The Suquía River Basin (Córdoba, Argentina) An Integrated Study on its Hydrology, Pollution, Effects on Native Biota and Models to Evaluate Changes in Water Quality (The Handbook of Environmental Chemistry,, 2018)
This book covers all relevant aspects involved in conducting water quality surveys of rivers. Focusing on the Suquía River (Argentina), it starts with a description of its hydrology and hydraulics before discussing the spatial and temporal changes in its water quality. A short chapter is dedicated to its limnology and particular characteristics due to the presence of a constructed dam and reservoir. Further chapters explore the changes in native biota inhabiting the river basin and assess various physical, chemical and microbiological parameters, as well as organic pollutants, metals and metalloids resulting from human activities. The book closes with a chapter providing an integrated approach to surveying river water quality, focusing on methods for data mining, from the simple use of water quality indexes to more formal mathematical-statistical methods (chemometrics) for evaluating changes in water quality. The book offers an invaluable reference guide for all environmental managers and scientists involved in water resources, their quality and management.